A framework of mobile learning acceptance and usage for micro-enterprises - Umami, Izzatul (2025)
The adoption of information and communication technology (ICT) is a critical concern for micro businesses, which are key contributors to national employment and economic development. The digital transformation of micro business actors is essential for promoting inclusive economic growth and resilience. This study aims to develop and test a framework for the acceptance and use of mobile-based learning technology (Mobile Learning) among micro business actors. The framework integrates the Technology Acceptance Model (TAM), the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), and the DeLone & McLean Information Systems Success Model. The three core variables of the framework are Entrepreneurial Readiness (ER), System Acceptance and Usage (AUS), and System Net Benefit (NBS). This research adopts a quantitative approach with a predictive focus, utilizing Partial Least Squares Structural Equation Modelling (PLS-SEM) along with experimental testing to validate the acceptance and use of the technological framework. A total of 237 micro business actors in the food industry in Jombang, East Java, Indonesia, were selected using purposive sampling. Data were collected via Google Forms distributed online through WhatsApp, Instagram, Telegram, and Facebook. The results show that AUS serves as a strong mediator between ER and NBS. The R² value for NBS was 0.933, indicating high predictive power in capturing the perceived benefits of the system. Path coefficients revealed strong direct influences from ER to AUS (β = 0.834) and from AUS to NBS (β = 0.766), with T-statistics exceeding the threshold of 1.96 (T > 11.0). In non-functional testing, the System Usability Scale (SUS) was administered to 37 system users, yielding an average score of 77.2 (classified as "good"), suggesting that the system is both user-friendly and widely accepted. Technical performance tests using Apache JMeter supported the Facilitating Condition indicator, demonstrating the system's stability under user loads typical for micro-enterprise operations. This research contributes to the development of a framework for technology acceptance and use, particularly, mobile learning strategies applied to business legality systems. The findings offer practical recommendations for micro business actors, policymakers, and technology developers to design more accessible and effective digital solutions that enhance the competitiveness and sustainability of micro enterprises. Future studies should expand the testing of this framework across different sectors and regions and explore integrations with adaptive technologies and artificial intelligence for personalized learning experiences.